SIMPEL (Sistem Informasi Manajemen Pelatihan) Internal BRI Menggunakan Metode Agile dengan Model Extreme Programming dan Algoritma Brute Force - Anang Kurniawan; Fauziah (KITA Institute, 2023)
This research develops SIMPEL (Training Management Information System) Internal BRI using Agile Methods, especially the Extreme Programming (XP) Method, and the Brute force Algorithm as a tool. XP is used because it is known as a method that is fast and flexible in accommodating changing user needs. The Brute force algorithm is implemented to help users search for training or similar information. White Box Testing is carried out to test the algorithm and shows that the time needed to find a participant data value is 0.43 ms. The results of this study indicate that the use of Agile Methods and Brute force Algorithms can increase efficiency and flexibility in software development.